Psychoanalytic diaries of the COVID-19 pandemic - Goisis, Pietro Roberto; Moroni, Angelo Antonio (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This intimate book explores the experiences of two psychoanalysts during the COVID-19 pandemic. It presents Angelo Moroni's psychoanalytic diary and Pietro Roberto Goisis's clinical diary, two highly personal perspectives that explore the interplay of the personal and the psychoanalytic during a time of collective trauma. Angelo's account, written from his 'camp tent', examines how fundamental, time-tested procedures are suddenly questioned. Roberto's diary is the story of his own experience as a COVID patient, the mutually therapeutic caring relationships he encounters and his efforts to keep his analytical expertise alive and well. The two accounts share painful and graphic experiences of the trauma of the pandemic, and how the authors were forced to reconsider the issues of analytical 'asymmetry' and 'neutrality'. Psychoanalytic Diaries of the COVID-19 Pandemic will be of great interest to psychoanalysts in practice and in training, and to readers with an interest in clinical and personal accounts of the COVID-19 pandemic"--
Keywords: COVID-19 (Disease) -- Psychological aspects; COVID-19 (Disease) -- Diaries; Psychotherapy; Psychoanalists -- Italy -- Biography; PSYCHOLOGY / Movements / Psychoanalysis; PSYCHOLOGY / Mental Health